Seismic retrofit of reinforced concrete strong beam–weak column joints using EBROG method combined with CFRP anchorage system. (1st September 2019) - Ilia, Elaheh; Mostofinejad, Davood
Highlights: Deficient exterior RC joints were constructed and tested under reverse cyclic loading. Proposed strengthening schemes provided a more ductile behavior for joint specimens. Seismic capacity of the retrofitted specimens was significantly increased. EBROG method together with CFRP fans eliminated any debonding or slipping of the FRP. Abstract: Beam-column assemblies of many existing reinforced concrete (RC) buildings are typically designed and built before the development of the current seismic codes; that may permanently fail in non-ductile behaviors, including column flexural hinging or joint shear failure mode, during ground motions. The current experimental research, therefore, was conducted to evaluate the efficiency of newly proposed rehabilitation schemes in retrofitting of deficient RC beam-column connections using fiber reinforced polymers (FRPs). To do so, five half-scale exterior beam-column joints were constructed and tested under constant axial and reversal-cyclic lateral loadings. The joint specimens were designed with strong beam-weak column theory and insufficient transverse reinforcement in the joint region. Of these, four specimens were strengthened with CFRP sheets and the remaining specimen was used as a control. In the strengthening patterns, to eliminate any surface debonding of FRP, the recently developed externally bonded reinforcement on grooves (EBROG) method was used. Besides, CFRP anchor fans were employed in the beam-column interface to completely anchor the longitudinal FRP sheets and also transfer the forces between the beam and the column. The test results showed that the adopted strengthening schemes successfully prevented the brittle failure of the specimens and were able to provide a more ductile mechanism by relocating the plastic hinge away from the weak column and the joint zone toward the beam. Furthermore, a significant enhancement was observed for specimens in terms of their strength, ductility and energy dissipation up to 73%, 139%, 144%, respectively. Additionally, the EBROG technique together with the CFRP fans at the interface of the beam-column joints eliminated any debonding or slipping of the longitudinal CFRPs.